How to Achieve Universal Health Coverage: A Case Study of Uganda Using the Political Process Model; Comment on “Health Coverage and Financial Protection in Uganda: A Political Economy Perspective” - Eusebio, Cidalia; Bakola, Maria; Stuckler, David (Kerman University of Medical Sciences, 2023)
How can resource-deprived countries accelerate progress towards universal health coverage (UHC)? Here we extend the analysis of Nanini and colleagues to investigate a case-study of Uganda, where despite high-level commitments, health system priority and funding has shrunk over the past two decades. We draw on the Stuckler-McKee adapted Political Process model to evaluate three forces for effecting change: reframing the debate; acting on political windows of opportunity; and mobilising resources. Our analysis proposes a series of pragmatic steps from academics, nongovernmental organisations, and government officials that can help neutralise the forces that oppose UHC and overcome fragmentation of the pro-UHC movement.